Science on the web: The exploration of European research websites of energy-related projects as digital genres for the promotion of values. (June 2020) - Lorés, Rosa
Highlights: EU research websites point at continuity with existing offline genres rather than change. A system of positive values, socially constructed, is projected in homepages. Evaluation reveals an ideology and it also shows potential as discourse organiser. The main aim of EU research websites is to account for public investment in research and innovation. Abstract: Digital discourse in scholarly and scientific communication has lately become a main object of study in discourse analysis, linguistics and associated fields. The increasing demands placed on scientists to disseminate and gain visibility for their research and on institutions to account for expenditure on research and innovation, in combination with a myriad of technical affordances, are enhancing the appearance of diverse digital practices, as a way to respond to an ever-changing and increasingly-demanding world. Within this context, the present study explores European Horizon 2020 websites dealing with research projects on energy as generic instances of current digital scientific practices. A special focus is placed on the use of evaluative language in their homepages and about pages in the understanding that evaluative language mirrors the values promoted in scientific research nowadays. In the webpages under analysis the main values promoted are the ones which are attached to two recurrent terms: project and energy . The study also shows the role that evaluative language plays in the construction of argument as discourse organiser. Moreover, the study reveals that, as textual instances, homepages and about pages do not differ much from offline genres, as they do not seem to fully exploit the technical affordances that the digital mode offers. However, they also seem to be subjected to a certain degree of recontextualization. In all, we might point at continuity rather than change in these generic instances.